Diffusion length of singlet excitons in copper phthalocyanine films - Signerski, Ryszard; Jarosz, Grazyna (Photonics Letters of Poland, 2011)
The work presents a method of extraction of exciton diffusion length from photocurrent spectrum measurements. A copper phthalocyanine (CuPc) layer was taken into consideration as an example. Samples were made in a high vacuum system by subsequent evaporation of the following layers: N, N’-dimethyle-3,4,9,10-perylenbis(dicarboximide) (MePTCDI) and CuPc and Au onto glass/ITO substrate. The subject of our investigation was a saturation photocurrent generated by exciton dissociation at MePTCDI/CuPc interference. As a result of our analysis, the product of quantum efficiency of exciton dissociation and charge carrier collection and exciton diffusion length was estimated and it yielded 1.6nm. Full Text: PDF References M. Pope, Ch. Swenberg, Electronic Processes in Organic Crystals and Polymers (New York, Oxford University Press 1999). P. Peumans, A. Yakimov, S.R. Forrest, "Small molecular weight organic thin-film photodetectors and solar cells", J. Appl. Phys. 93, 3693 (2003)[CrossRef] M. Riede, T. Mueller, W. Tress, R. Schueppel, K. Leo, "Small-molecule solar cells—status and perspectives", Nanotechnology 19, 1 (2008)[CrossRef] A.W. Hains, Z. Liang, M.A. Woodhouse, G.A. Gregg, "Molecular Semiconductors in Organic Photovoltaic Cells", Chem. Rev. 2010, 110 (11), pp 6689–6735[CrossRef] Y. Zheng, J. Xue, "Organic Photovoltaic Cells Based on Molecular Donor-Acceptor Heterojunctions", Polymer Reviews 50, 420 (2010)[CrossRef] V.M. Kenkre, P.E. Parris, D. Schmid, "Investigation of the appropriateness of sensitized luminescence to determine exciton motion parameters in pure molecular crystals", Phys. Rev. B32, 4946 (1985)[CrossRef] S.R. Scully, M.D. McGehee, "Effects of optical interference and energy transfer on exciton diffusion length measurements in organic semiconductors", J. Appl. Phys. 100, 034907 (2006)[CrossRef] R.R. Lunt, N.C. Giebink, A.A. Belak, J.B. Benziger, S.R. Forrest, "Exciton diffusion lengths of organic semiconductor thin films measured by spectrally resolved photoluminescence quenching", J.Appl. Phys. 105, 053711 (2009)[CrossRef] Y. Vertsimakha, P. Lustyk, K. Palewska, J. Sworakowski, O. Lytvyn, "Optical and photovoltaic properties of thin films of N,N'-dimethyl-3,4,9,10-perylenetetracarboxylic acid diimide", Thin Solid Films 515, 7950 (2007)[CrossRef] G. Jarosz, R. Signerski, J. Godlewski, Acta Physica Polonica A 87, 855 (1995). A.K. Ghosh, T. Feng, "Merocyanine organic solar cells", J. Appl. Phys. 49, 5982 (1978)[CrossRef] S.-B. Rim, P. Peumans, "The effects of optical interference on exciton diffusion length measurements using photocurrent spectroscopy", J. Appl. Phys. 103, 124515 (2008)[CrossRef] T. Osasa, Y. Matsui, T. Matsumura, M. Matsumura, "Determination of photo-active region in organic thin film solar cells with an organic heterojunction", Solar Energy Materials and Solar Cells, 90, 3136 (2006)[CrossRef] L.A.A. Pettersson, L.S. Roman, O. Ingan?s, "Modeling photocurrent action spectra of photovoltaic devices based on organic thin films", J. Appl. Phys. 86, 487 (1999)[CrossRef] T. Stubinger, W. Brutting, "Exciton diffusion and optical interference in organic donor–acceptor photovoltaic cells", J. Appl. Phys. 90, 3632 (2001)[CrossRef] Ch. Breyer, M. Vogel, M. Mohr, B. Johnev, K. Fostiropoulos, "Influence of exciton distribution on external quantum efficiency in bilayer organic solar cells", Phys. Stat. Sol. (B) 243, 3176 (2006)[CrossRef] L.-G. Yang, H.Z. Chen, M. Wang, "Optimal film thickness for exciton diffusion length measurement by photocurrent response in organic heterostructures", Thin Solid Films 516, 7701 (2008)[CrossRef] Y. Terao, H. Sasabe, C. Adachi, "Correlation of hole mobility, exciton diffusion length, and solar cell characteristics in phthalocyanine/fullerene organic solar cells", Appl. Phys. Lett. 90, 103515 (2007)[CrossRef] R. Signerski, G. Jarosz, "Effect of buffer layers on performance of organic photovoltaic devices based on copper phthalocyanine-perylene dye heterojunction", Opto-Electronics Review 19, 468 (2011)[CrossRef] N. Minami, M. Asai, "Photocurrent Spectra of Phthalocyanine Films in Relation to Excited State Properties", Jap. J. Appl. Phys. 26, 1754 (1987)[CrossRef] L.M. Blinov, S.P. Palto, A.A. Vdalyev, Mol. Mat. 1, 65 (1992). M. Knupfer, T. Schwieger, H. Peisert, J. Fink, "Mixing of Frenkel and charge transfer excitons in quasi-one-dimensional copper phthalocyanine molecular crystals", Phys. Rev. B 69, 165210 (2004)[CrossRef] M. Wojdyła, B. Derkowska, W. Bała, A. Bratkowski, A. Korcala, Optical Materials 28, 1000 (2006). S.-B. Rim, R.F. Fink, J.C. Schoneboom, P. Erk, P. Peumans, "Effect of molecular packing on the exciton diffusion length in organic solar cells", Appl. Phys. Lett. 91, 173504 (2007)[CrossRef]